The uneasy partnership - Safetycare Australia Pty. Ltd. ([S.l.] : Safetycare Australia, 1988)
Documentary about fire prevention procedures that involve the identification of specific fire hazards - hazards that exist in workplace.
Accompanied by 1 trainer's manual
Copy available in DVD format
Keywords: Hazardous wastes -- Risk assessment; Fire risk assessment